Analisis Komparatif Pemikiran Ekonomi Al-Ghazali dan Al-Mawardi - Merandi, Erwin; Riswan; Alfarezi, Muhammad (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2024)
The study of classical Muslim scholars' economic thought provides valuable insights for the development of contemporary economics. This research specifically analyzes and compares the economic ideas of two significant figures in the history of Islamic economic thought: Al-Ghazali and Al-Mawardi. Al-Ghazali, with his emphasis on ethics and market mechanisms, and Al-Mawardi, who focused on the role of the state in economic management, each made significant contributions to the treasury of Islamic economic thought. The research employs a literature review method by analyzing their key works, namely Ihya Ulumuddin, al-Mustasfa, and Nasihat al-Muluk (by Al-Ghazali) as well as Al-Ahkam as-Sulthaniyyah (by Al-Mawardi). The findings indicate that despite their differing focal points—individual ethics versus institutional regulation—their ideas complement each other in providing a comprehensive perspective on Islamic economics. Furthermore, this study concludes that their economic thoughts remain relevant and applicable in analyzing and addressing contemporary economic issues.